Gas permeability of amphiphilic block-copolymers polyisobornylacrylat-polyacrylic acid - Yu. О. Кirilina; W. Van Camp; I. V. Bakeeva; F. E. Du Prez; V. A. Tverskoy; V. P. Zubov (Тонкие химические технологии)
Amphiphilic block-copolymers of polyisobornylacrylate-polyacrilic acid synthesized by means of ATRP were used for producing of membrane. Gas permeability measurements were carried out on individual gases: carbon dioxide, oxygen, nitrogen